2021
DOI: 10.1002/oby.23261
|View full text |Cite
|
Sign up to set email alerts
|

Associations of midchildhood to early adolescence central adiposity gain with cardiometabolic health in early adolescence

Abstract: Objective This study examined the associations of central adiposity gain from midchildhood to early adolescence with cardiometabolic health markers in early adolescence. Methods A total of 620 participants were studied in Project Viva. In midchildhood (mean age = 7.8 years) and early adolescence (12.9 years), waist circumference and dual‐energy x‐ray absorptiometry‐measured visceral adipose tissue, subcutaneous abdominal adipose tissue, and trunk fat were obtained. Central adiposity gain was calculated as chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Importantly, our observations revealed that "unhealthy" subjects among children without obesity was 41% (T2), 38% (T4) and 30% (1YPM), which should be a reason for concern. Central fat accumulation in childhood into adolescence has been directly associated with unfavorable cardiometabolic health marker profiles, regardless of total body fat 37 . Our results indicate that at T2, HOMA-IR was directly correlated with WC but not with zBMI, in children classified as metabolically-unhealthy (data not shown), consistent with a more relevant role of central than whole body fatness inducing metabolic derangements.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our observations revealed that "unhealthy" subjects among children without obesity was 41% (T2), 38% (T4) and 30% (1YPM), which should be a reason for concern. Central fat accumulation in childhood into adolescence has been directly associated with unfavorable cardiometabolic health marker profiles, regardless of total body fat 37 . Our results indicate that at T2, HOMA-IR was directly correlated with WC but not with zBMI, in children classified as metabolically-unhealthy (data not shown), consistent with a more relevant role of central than whole body fatness inducing metabolic derangements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have already found those with a greater change in BMI during adolescence have increased future insulin resistance ( 38 ). Some have even begun evaluating trends of different adiposity measurements as they relate to short term outcomes ( 39 , 40 ). As cohorts progress in age, additional studies of trajectories of other measures of adiposity, aside from BMI, on long term disease risk may reveal potential benefits to alternative measurements.…”
Section: Patterns In Adiposity Changementioning
confidence: 99%
“…Some researchers would assert overfat as an excess of body fat percentage (BF%) [7,12], and others would suggest using fat mass index (FMI) [10,13]. Furthermore, a growing amount of evidence suggests that general and abdominal fat measures can provide complementary information to each other for cardiometabolic risk (CMR) prediction [14][15][16]. However, how to choose and combine these body fat indicators to maximize their utility in risk stratification among children has not been established so far.…”
Section: Introductionmentioning
confidence: 99%